(3cJGH GdbQGAI Nda GdEeGes - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3HGH hLhH bQGAI GdaGJMI GdcJGH ai cd QcYI s
(3BNQgG (B:s
(3Yf CHj gQjQI bGd CeQfi GdfHi Udi Gddg Ydjg hSde Cf CfGOi Cf dG UdGI EdG HbQGAI aGJMI GdcJGH aeG RGO s
(3GdfSNI HgG MhGTs
(3YdjgG SeGYGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
Keywords: (3GdMOjK h GdeUWdMs